CFD for liquid-liquid dispersed flows in horizontal pipe - Walvekar, Rashmi G.; Hussain, Siti Aslina; Choong, Thomas Shean Yaw (Federation of Engineering Institutions of Islamic Countries, 2006)
Computational Fluid Dynamics (CFD) code, FLUENT 6.2 was used to study dispersed flows in horizontal pipe. Oil-water system is chosen as the fluids of interest with water as the continuous and oil as the dispersed phase. Velocity magnitude, phase distribution profiles, pressure profiles, is presented in this paper. The objective of the research was to check the capability and applicability of the code for multiphase flows. The simulation of dispersed flow was carried out in a horizontal tube of 0.024m ID and 9.5m length. The hold-up and pressure profiles are compared with previous research work to validate the present work. The compared results were in good agreement with the experimental ones.